Kesejahteraan Psikologis Ditinjau Dari Kebersyukuran dan Resiliensi Peserta Didik - Muhammad Hamdan Andrysof Taifur; Zarina Akbar; Iriani Indri Hapsari (Publikasi Indonesia, 2026)
Adolescents are a group that is more susceptible to mental health disorders compared to individuals in the young adult stage and late adulthood. This condition is related to the low level of psychological well-being, so this aspect is very important in the adolescent development process. Two factors that are believed to play a role in improving psychological well-being are gratitude and resilience. Gratitude reflects an individual's ability to appreciate the positive things in life, while resilience describes the ability to adapt and rise from various difficulties. This study used a causal quantitative design with 116 participants of high school students in Jakarta obtained through convenience sampling techniques. Data collection was carried out using three instruments, namely the Psychological Well-Being Short Scale (18 items), the Gratitude, Resentment, and Appreciation Test (GRAT), and the Connor-Davidson Resilience Scale (CD-RISC 25). Data analysis was carried out using multiple linear regression with the help of SPSS version 23.The results showed that gratitude and resilience had a significant effect on psychological well-being, both simultaneously and partially. Adolescents who are able to appreciate the positive aspects of their lives, are adaptive, and have the ability to rise from problems have good psychological well-being. Therefore, psychological interventions that focus on developing gratitude and resilience can be an effective strategy in improving students' psychological well-being.